Corporate Governance Success Stories - International Finance Corporation (World Bank, Cairo, 2016)
This report summarizes the experiences of 19 companies from across the region. Each of the case studies highlights the key corporate governance changes made and the positive impacts that resulted, as reported by the company. The companies represent various countries, sectors, types, and sizes. All of the companies featured are former IFC Advisory Services clients. Some are IFC Investment clients as well. IFC conducted an in-depth corporate governance assessment for each of these companies using IFC’s Corporate Governance Methodology. The assessments resulted in specific recommendations on ways to improve each company’s governance framework and identified implementation plans. The assessments were conducted at various points over the past few years. The time taken to implement changes and realize benefits varied. However, all companies reported that governance changes are continuous and the corresponding benefits manifest themselves in different forms over time. This report provides examples of companies in various stages of change – from recent changes (e.g., Medgulf) to ongoing, longer-term changes (e.g., Bank Audi). This report also includes testimony from three MENA private equity firms (all IFC investment clients). Collectively, these firms have worked with 72 investee companies (past and present funds). Selected based on their association with IFC and their willingness to share their insight and experiences, these firms offer a valuable window into the importance of corporate governance from an investor’s perspective. The material in this report is based on feedback gathered through individual interviews with each organization featured, resulting in well-considered responses. The achievements highlighted are all the more notable given that the interviews and information gathering process took place in in late 2009 (first edition) and 2013 (for current edition), when the region was still under the stress of the crisis.